Non-Invasive Evaluation of Egg Quality and Early Life Stage Development of Medaka Fish (Oryzias latipes) by Means of Morphological Image Analysis Methods - Kriščiukaitis, A.; Webb, D. J.; Grigaliūnas, A. (Elektronika ir Elektrotechnika, 2009)
Early life stage animal models are used to investigate environmental contamination by various industrial wastes and toxicity of various potential drugs or substances used in the production of clothes and food. Estimation of chances of the survival of particular fauna species facing global environmental changes is also done using the same models. This study demonstrates how advanced image processing methods applied for evaluation of egg quality and investigation of the development of the embryos of the fresh water teleost fish, medaka (Oryzias latipes) could extend the possibilities and improve the quality of investigations. Quality of the egg (evoked cortical reaction) and development of the cardiovascular system of the embryo were evaluated using methods of mathematical morphology. Optical registration of the heart beats of the embryos combined with advanced signal processing methods were used for detailed analysis of heart activity. All these methods could be applied to detect and evaluate the developmental disorders of the embryos – indicators of environmental contamination or toxicity of chemical substances. Ill. 5, bibl. 15 (in English; summaries in English, Russian and Lithuanian).